Vitamin D–Dependent Rickets Type 1B (25‐Hydroxylase Deficiency): A Rare Condition or a Misdiagnosed Condition?. (13th July 2017) - Molin, Arnaud; Wiedemann, Arnaud; Demers, Nick; Kaufmann, Martin; Do Cao, Jérémy; Mainard, Laurent; Dousset, Brigitte; Journeau, Pierre; Abeguile, Geneviève; Coudray, Nadia; Mittre, Hervé; Richard, Nicolas; et al.
ABSTRACT: Vitamin D requires a two‐step activation by hydroxylation: The first step is catalyzed by hepatic 25‐hydroxylase ( CYP2R1, 11p15.2) and the second one is catalyzed by renal 1α‐hydroxylase ( CYP27B1, 12q13.1), which produces the active hormonal form of 1, 25‐(OH)2 D. Mutations of CYP2R1 have been associated with vitamin D–dependent rickets type 1B (VDDR1B), a very rare condition that has only been reported to affect 4 families to date. We describe 7 patients from 2 unrelated families who presented with homozygous loss‐of‐function mutations of CYP2R1 . Heterozygous mutations were present in their normal parents. We identified a new c.124_138delinsCGG (p.Gly42_Leu46delinsArg) variation and the previously published c.296T>C (p.Leu99Pro) mutation. Functional in vitro studies confirmed loss‐of‐function enzymatic activity in both cases. We discuss the difficulties in establishing the correct diagnosis and the specific biochemical pattern, namely, very low 25‐OH‐D suggestive of classical vitamin D deficiency, in the face of normal/high concentrations of 1, 25‐(OH)2 D. Siblings exhibited the three stages of rickets based on biochemical and radiographic findings. Interestingly, adult patients were able to maintain normal mineral metabolism without vitamin D supplementation. One index case presented with a partial improvement with 1alfa‐hydroxyvitamin D3 or alfacalcidol (1α‐OH‐D3 ) treatment, and we observed a dramatic increase in the 1, 25‐(OH)2 D serum concentration, which indicated the role of accessory 25‐hydroxylase enzymes. Lastly, in patients who received calcifediol (25‐OH‐D3 ), we documented normal 24‐hydroxylase activity ( CYP24A1 ). For the first time, and according to the concept of personalized medicine, we demonstrate dramatic improvements in patients who were given 25‐OH‐D therapy (clinical symptoms, biochemical data, and bone densitometry). In conclusion, the current study further expands the CYP2R1 mutation spectrum. We note that VDDR1B could be easily mistaken for classical vitamin D deficiency. © 2017 American Society for Bone and Mineral Research.